Measurement errors in recall food consumption data - Naeem Ahmed; Matthew Brzozowski; Thomas F. Crossley (Institute for Fiscal Studies (IFS), 2006)
Recall food consumption data, which is the basis of a great deal of empirical work, is believed to suffer from considerable measurement error. Diary records are believed to be very accurate. We study a unique data set that collects recall and diary data from the same households. Measurement errors in recall food consumption data appear to be substantial, and they do not have the properties of classical measurement error. We also find evidence that the diary measures are themselves imperfect. We consider the implications of our findings for modelling demand, measuring inequality, and estimating inter-temporal preference parameters. – expenditure ; consumption ; measurement error ; survey data
Keywords: C81; D12; 330